PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMAKAIAN JASA (Studi Kasus Pada PT. Nasmoco Majapahit Semarang) - Danang Prakoso; Hari Susanta Nugraha; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2013)
Variable prices and the quality of service is a contributing factor to the decision to use consumer services on repair shop PT. Nasmoco Majaphit Semarang. When the perception of customer to price is good and high quality of services, the high level of service consumption decisions as well, and vice versa. The formulation of the problem in this research is still not achieve the target use of the service as a whole, has reached between 80%-95%, on the other hand the workshop PT. Nasmoco Majapahit Semarang had set a price that can compete with other workshop, and also sets a high standard of service quality.The type of research that is used is explanatory research. Data collection techniques by using a questionnaire which was distributed to 100 respondents from the consumer workshops PT. Nasmoco Majapahit Semarang. The Data were analyzed qualitatively and quantitatively analysis numbers without using the test of validity, reliability, determination of test, a simple linear regression, multiple linear regression, T-test, F-test, and with the help of Cuckold Kelly wells.The conclusion of the research is the  consumer perceptions to price is good the quality of service and a decision discharging services is high. The result analysis proving that prices in partial prices have influence of the decision of discharging services 35.9 %, is as much as while the service quality of having influence of the decision use services by 18.7 %. Then simultaneously variable prices and service quality has an influence to use services decision worth 39 %.Suggestions that can be delivered are in terms of price, service station PT. Nasmoco Majapahit Semarang should pay attention to even the discounted price with the requirements to be met more easily. Then in terms of the quality of service workshop PT. Nasmoco Majapahit Semarang should pay more attention to the accuracy of the results of the tune up compared to the offer, and also the ability of employees who are less prevalent in doing the tune up